The Managerial Experience and Postgraduate University Training of School Principals: A Comparison of Two Post-Socialist Countries Using TIMSS 2015 and PIRLS 2016 Data - Želvys, Rimantas; Esenova, Kamchat; Rakhymberdiyeva, Ainur (Acta Paedagogica Vilnensia, 2019)
Contemporary research on education policies and practices of post-socialist countries is not expansive. According to our understanding, there are at least several reasons for a rather limited interest of researchers. There is no single, universally accepted theoretical approach to post-socialist development; territorial disputes pose problems to statistical data analysis; some countries with authoritarian regimes tend to play with the data and improve the numbers; there are difficulties of finding the data about non-EU countries. One of the possibilities of conducting comparative studies is the usage of international large-scale assessments (ILSAs). The aim of our study was to highlight the different attitudes toward the training of school principals in Lithuania and Kazakhstan on the basis of a secondary analysis of TIMSS 2015 and PISA 2016 data. Results indicate that there are essential differences between the two countries. The percentage of students in schools where Lithuanian school principals have undergone postgraduate university training exceed the percentage of students in Kazakhstani schools 4 to 5 times. Lithuanian school principals also have, on average, 1.5 times longer professional experience than Kazakhstani school principals. However, data of TIMSS 2015 and PIRLS 2016 show no direct relationship between the level of education and work experience of school principals and student achievement. We assume that higher professionalism and experience of school principals may contribute to the efficiency of school management, while the effectiveness of student learning may be determined by a variety of other factors.
Keywords: post-socialist education; TIMSS 2016; PIRLS 2016; school principals’ work experience and postgraduate university training in Lithuania and Kazakhstan